Pengaruh pemberian dedak padi yang difermentasi dengan cairan isi rumen terhadap performans burung puyuh (Coturnix coturnix japonioca) jantan - Marni Nababan; Lisnawaty Silitonga; Budya Satata (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2017)
The aim of this research was to know the effect of rice bran fermented with rumen fluid contents on the performances of male quail (Coturnix coturnix japonioca). This research was designd by Completely Randomized Design (CRD). Sixty (60) quail were grouped into four and five replication, each replication consists of three quails. The treatment were P0 (feed basal 100%), P1 (feed basal 95% + rice bran fermentation 5%), P2 (feed basal 90% + rice bran fermentation 10%), P3 (feed basal 85% + rice bran fermentation 15%). The results showed that each treatments were not significant differences on feed consumption, body weight gain, and feed conversion. The treatment of fermented rice bran 5% for quail males, give positive response to observed variables.